Właściwości lecznicze grzybów wielkoowocnikowych - Hilszczańska, Dorota (Leśne Prace Badawcze, 2012)
This review highlights the importance to people of some types of wild fungi considered in the context of non-wood forest products. Macrofungi are used both for food and medicine proposes. Substances isolated from the higher Basidiomycetes and Ascomycetes mushrooms express promising immune modulating, antitumor, antiviral, antibacterial and antidiabetic properties. They have been, and are presently, used against cancer in some countries in Far East as well as in the United States of America and Canada. Their useful properties are mainly conferred by biologically-active polysaccharides present in the fruiting bodies and cultured mycelium. A few dozen different polysaccharide antitumor agents have been developed from such species as: Ganoderma lucidum , Lentinus edodes , Schizophylum commune , Trametes versicolor and Inonotus obliquus . In the review some other fungi and their properties are also described. The information is provided to widen our knowledge of the importance of the organisms that live in forest ecosystems.